New instruments of monetary policy - Jagjit S. Chadha; Sean Holly (University of Kent, School of Economics, 2011)
We assess recent developments in monetary policy practice following the financial crisis drawing on papers from a specially convened conference in March 2010. In particular, we consider why central banks throughout the world have injected substantial quantities of liquidity into the financial system and seen their balance sheets expand to multiples of GDP. We outline the rationale for balance sheet operations: (i) portfolio balance of the non-bank financial sector; (ii) an offset for the zero bound; (iii) signalling mechanism about medium term inflation expectations and (iv) the alleviation of the government's budget constraint. We briefly outline the recent experience with QE and draw a distinction between liquidity and macroeconomic stabilisation operations.
Keywords: E31; E40; E51; 330; zero bound; open-market operations; quantitative easing; monetary policy